Human Milk Bank: Strategy For The Reduction Of Neonatal Morbidity And Mortality - National Maternal Perinatal Institute - León-Mauricio, Zulema Frieda (2016)
The National Maternal Perinatal Institute (INMP), within the strategies implemented with the objective of reducing the morbidity andmortality rate with the technical advice of Brazil, inaugurated in 2010 the first Human Milk Bank of the country, with the purpose offeeding With mother’s milk from her own mother or with breast milk donated pasteurized, totally or partially to the preterm born inour institution, primarily to those born with a weight ≤ 1500 grams, as well as to post-surgical newborns. The BLH Responsible foractions of promotion, protection and support to breastfeeding, performs the processes of procuring (donor recruitment, lactationcounseling, etc); Processing or pasteurization of human milk (from this process comes safe milk) and fractionation and distributionaccording to medical indication. In order to carry out our work, we have the support of our collection centers, as well as the motherswho show solidarity within and outside the INMP, and donate the surplus of their milk, to support us in achieving the goal.